👤
Kimberlyeli
a fost răspuns

1 + 3 + 5+ 7 + ... + 2009 + 2011-2-4-6-... - 2008​

Răspuns :

Răspuns:

3006

Explicație pas cu pas:

1 + 3 + 5+ 7 + ... + 2009 + 2011-2-4-6-... - 2008​

Suma lui Gauss  1+2+3+...+n=n·(n+1)/2

1 + 3 + 5+ 7 + ... + 2009 + 2011= (1+2+3+...+2011)-(2+4+6+...+2010)= 2011·2012/2-2(1+2+3+...+1005)= 2011·1006-2·1005·1006/2= 2011·1006-1005·1006=1006(2011-1005)=1006·1006

1 + 3 + 5+ 7 + ... + 2009 + 2011-2-4-6-... - 2008​= 1006·1006-2(1+2+3+...+1004)=1006·1006-2·1004·1005/2= 1006·1006-1004·1005= 1012036- 1009020=3006